Experimental investigation of the effect of TDS on the thermal performance of the different types of solar stills - Hind I. El-Refaey; Saleh. M. Shalaby; Swellam W. Sharshir; Hewida Omara; Tamer A. Gado (AIMS Energy)
In regions with a restricted availability of drinkable water, solar stills offer a solution for a passive solar desalination method. In this study, three designs for solar stills are examined: the conventional solar still (CSS), the hemispheric solar still (HSS), and the pyramidal solar still (PSS). The experimental investigations were conducted over three consecutive days, thereby varying the total dissolved solids (TDS) concentrations in the basin water at 1000, 2000, and 3000 ppm. A comparative analysis focused on the performance of the various solar stills and the impact of TDS variation. The results revealed that the PSS consistently outperformed the CSS and HSS across all TDS levels. Notably, the PSS exhibited superior daily energy and exergy efficiencies. Furthermore, the daily productivity and energy efficiencies displayed an inverse relationship with the TDS concentration. A cost analysis indicated that the PSS achieved the lowest distilled water price, reaching a value of 0.0151 ＄/L. Specifically, the PSS exhibited a 17.3% and 3.5% higher accumulated daily productivity compared to CSS and HSS, respectively, at TDS = 1000. However, at TDS = 3000, the daily productivity of the PSS decreased by 3.5% and 7.5% compared to TDS = 2000 and 1000, respectively. Similarly, the energy efficiency of the PSS decreased by 5.27% and 8.67% as the TDS increased from 1000 to 3000. Notably, across all solar still types, the lowest cost values were consistently associated with the lowest TDS concentrations, with the PSS yielding the lowest cost overall.